Carbamazepine-induced Stevens Johnson syndrome: a case series of three case reports - Kumar, Arvind; Kansal, Dinesh; Chaudhary, Usha Kumari; Sharma, Ajay; Sharma, Reena (International Journal of Basic & Clinical Pharmacology, 2017)
Carbamazepine is an iminostilbene derivative that was initially used as an antiepileptic but has been used with increased frequency for different indications including chronic pain, trigeminal neuralgia, and herpetic neuralgias. This has resulted in increased incidence of carbamazepine related adverse effects such as nausea, vomiting, and serious hematological toxicities such as aplastic anemia, agranulocytosis, eosinophilia, lymphadenopathy, and splenomegaly. Life-threatening hypersensitivity reactions such as Steven Johnson syndrome (SJS) and toxic epidermal necrolysis can also occur. We hereby present a series of three cases that were prescribed carbamazepine for different indications and presented with SJS.